Trends in urethral stricture management over two decades. (22nd October 2019) - McGeorge, Stephen; Chung, Amanda; Desai, Devang J.
Abstract : Objectives: To identify trends in the management of urethral stricture disease in Australia, assess changes in the standard of care, and examine the availability of genitourinary reconstructive surgery. Methods: Data on eight stricture management procedures were collected online via Medicare Item Reports from the Australian Government Department of Human Services, and then matched to population data from the Australian Bureau of Statistics. A survey was disseminated via the Urological Society of Australia and New Zealand (USANZ) asking whether active members performed urethroplasty and whether this was done in a rural, regional or metropolitan setting. Results: Over a 22‐year period, there were 140 540 endoscopic procedures and 5136 urethroplasties, with 27.4 endoscopic procedures per urethroplasty. From 1994 to 2016, the per capita number of passage of sounds and dilatation procedures decreased by 74% and 75%, respectively, with increases in use of optical urethrotomy of 70% and in single‐stage urethroplasty of 144%. Overall, the ratio of all endoscopic procedures vs urethroplasty decreased from 58.9 to 16.8. There were as few as 16 surgeons in the USANZ performing urethroplasty, with seven providing this service in regional areas. Seven had formal fellowship training. Conclusion: There has been a clear shift from repetitive endoscopic procedures towards urethroplasty, but the former still make up the majority of interventions. This may be explained by patients not being referred for urethroplasty earlier in the course of disease and there appears to be a gap in genitourinary reconstructive expertise in regional and rural areas.